Ni(II) Butylmethyldithiocarbamate: Physico-Chemical Properties, X-Ray Crystallography, DFT and Anti-Corrosion Screening in Different Acids - Nor Farah Hida Othman; Noor Syafiqah Habdul Latif; Sheikh Ahmad Izzadin Sheikh Mohd Ghazali; Erna Normaya Abdullah; Nur Nadia Dzulkifli (ASM Science Journal, 2021)
In industrial sectors, pickling and acid cleaning are mutual processes where acid solutions, such as hydrochloric acid (HCl) and sulfuric acid (H2SO4), are used to eliminate the corrosion products yielded on metal surfaces; thus, improving the performance of the machineries. However, the usage of the acid could lead to another metal deterioration. Dithiocarbamate inhibitor is defined as an organic compound that has good corrosion inhibition properties that can work as an inhibitor in an acid environment. Dithiocarbamate (DTC) assists by reducing acid reactiveness which prohibits metal dissolution in the acid. In this study, the Ni(II) N-butylmethyldithiocarbamate (Ni[BuMedtc]2) complex was synthesised by using an in-situ method and characterised by elemental analyser, attenuated total reflection Fourier transform infrared (ATR-FTIR), ultraviolet-visible (UV-Vis) spectroscopy and X-ray crystallographic study, and the chemical properties of the Ni[BuMedtc]2 complex was successfully calculated by the Discrete Fourier Transform (DFT) approach. The experimental results which were obtained through the weight-loss analysis method in two different acids – 1 M HCl and 1 M H2SO4 – indicated that the inhibition efficiency increased as the inhibitor concentration increased. The outcome showed that the Ni[BuMedtc]2 performed better as an inhibitor in 1 M HCl as compared to in1 M H2SO4 to protect the metal exterior because H2SO4 is more corrosive due to the excessive presence of H+.